Determination of phenolic compounds and hydroxymethylfurfural in meads using high performance liquid chromatography with coulometric-array and UV detection - Kahoun, David; Rezková, Sona; Veskrnová, Katerina; Královský, Josef; Holcapek, Michal (Journal of chromatography. A, 2008)
The objective of this study was the determination of 25 phenolic compounds in different mead samples (honeywines) using high performance liquid chromatography (HPLC) with coulometric-array detection and in case of hydroxymethylfurfural with UV detection. Our method was optimized in respect to both the separation selectivity of individual phenolic compounds and the maximum sensitivity with the electrochemical detection. The method development included the optimization of mobile phase composition, the pH value, conditions of the gradient elution and the flow rate using a window-diagram approach. The developed method was used for the determination of limits of detection and limits of quantitation for individual compounds. The linearity of calibration curves, accuracy and precision (intra- and inter-day) at three concentration levels (low, middle and high concentration range) were verified. Mead samples were diluted with the mobile phase at 1:1 to 1:50 ratio depending on the concentration and filtered through a PTFE filter without any other sample pre-treatment. Phenolic compounds concentration was determined in 50 real samples of meads and correlated with meads composition and hydroxymethylfurfural concentration. The most frequently occurred compounds were protocatechuic acid and vanillic acid (both of them were present in 98% samples), the least occurred compounds were (+)-catechin (10% samples) and sinapic acid (12% samples). Vanillin and ethylvanillin, which are used as artificial additives for the taste improvement, were found in 60% and 42% samples, respectively. Hydroxymethylfurfural concentration, as an indicator of honey quality, was in the range from 2.47 to 158 mg/L. Our method is applicable for the determination of 25 phenolic compounds in mead, honey and related natural samples.
Keywords: molekulární struktura; Phenols; Reproducibility of Results; nápoje; Wine; Chromatography, High Pressure Liquid; Spectrophotometry, Ultraviolet; vysokoúčinná kapalinová chromatografie; spektrofotometrie ultrafialová; víno; reprodukovatelnost výsledků; Beverages; 2-furaldehyd; fenoly; Furaldehyde; Molecular Structure